History and symptom taking in contact lens fitting and aftercare. Issue 4 (August 2015) - Wolffsohn, James S.; Naroo, Shehzad A.; Christie, Caroline; Morris, Judith; Conway, Robert; Maldonado-Codina, Carole; Retalic, Neil; Purslow, Christine; The British Universities Committee of Contact Lens Educators (BUCCLE)
Abstract Aim To appraise history and symptom taking for contact lens consultations, to determine current practice and to make recommendations for best practice. Method The peer reviewed academic literature was reviewed and the results informed a survey completed by 256 eye care practitioners (ECPs) on their current practice and influences. Results The last eye-test date, last contact lens aftercare (for existing wearers) and reason for visit are key questions for most ECPs. Detailed use of contact lens questions are more commonly applied in aftercares than when refitting patients who have previously discontinued wear (87% vs 56% use), whereas questions on ocular and general history, medication and lifestyle were generally more commonly utilised for new patients than in aftercares (72% vs 50%). 75% of ECPs requested patients bring a list of their medication to appointments. Differential diagnosis questioning was thorough in most ECPs (87% of relevant questions asked). Attempts to optimise compliance included oral instruction (95% always) and written patient instructions (95% at least sometimes). Abbreviations were used by 39% of respondents (26% used ones provided by a professional body). Conclusion There is scope for more consistency in history and symptom taking for contact lens consultations and recommendations are made.